PREDICTION OF IDENTICAL TWINS USING ML (International Journal of Food and Nutritional Sciences, 2022)
The "Prediction of Identical Twins using ML" project seeks to develop a machine learning-based solution for accurately identifying identical twins from a population based on their physical characteristics and biometric data. Identifying identical twins is a complex task with significant implications in various fields, including healthcare, forensics, and even personalized marketing. Leveraging machine learning, this project aims to advance the state-of-the-art in twin identification, offering a novel and efficient approach to a longstanding challenge.